Pyruvate kinase M2 regulates homologous recombination-mediated DNA double-strand break repair. Issue 11 (November 2018) - Sizemore, Steven; Zhang, Manchao; Cho, Ju; Sizemore, Gina; Hurwitz, Brian; Kaur, Balveen; Lehman, Norman; Ostrowski, Michael; Robe, Pierre; Miao, Weili; Wang, Yinsheng; Chakravarti, Arnab; et al.
Abstract Resistance to genotoxic therapies is a primary cause of treatment failure and tumor recurrence. The underlying mechanisms that activate the DNA damage response (DDR) and allow cancer cells to escape the lethal effects of genotoxic therapies remain unclear. Here, we uncover an unexpected mechanism through which pyruvate kinase M2 (PKM2), the highly expressed PK isoform in cancer cells and a master regulator of cancer metabolic reprogramming, integrates with the DDR to directly promote DNA double-strand break (DSB) repair. In response to ionizing radiation and oxidative stress, ATM phosphorylates PKM2 at T328 resulting in its nuclear accumulation. pT328-PKM2 is required and sufficient to promote homologous recombination (HR)-mediated DNA DSB repair through phosphorylation of CtBP-interacting protein (CtIP) on T126 to increase CtIP's recruitment at DSBs and resection of DNA ends. Disruption of the ATM-PKM2-CtIP axis sensitizes cancer cells to a variety of DNA-damaging agents and PARP1 inhibition. Furthermore, increased nuclear pT328-PKM2 level is associated with significantly worse survival in glioblastoma patients. Combined, these data advocate the use of PKM2-targeting strategies as a means to not only disrupt cancer metabolism but also inhibit an important mechanism of resistance to genotoxic therapies.